Clinician preferences for verbal communication compared to EHR documentation in the ICU - Collins, S.A.; Bakken, S.; Vawdrey, D.K.; Coiera, E.; Currie, L. (Applied Clinical Informatics, 2011)
Background: Effective communication is essential to safe and efficient patient care. Additionally, many health information technology (HIT) developments, innovations, and standards aim to implement processes to improve data quality and integrity of electronic health records (EHR) for the purpose of clinical information exchange and communication.Objective: We aimed to understand the current patterns and perceptions of communication of common goals in the ICU using the distributed cognition and clinical communication space theoretical frameworks.Methods: We conducted a focus group and 5 interviews with ICU clinicians and observed 59.5 hours of interdisciplinary ICU morning rounds.Results: Clinicians used an EHR system, which included electronic documentation and computerized provider order entry (CPOE), and paper artifacts for documentation; yet, preferred the verbal communication space as a method of information exchange because they perceived that the documentation was often not updated or efficient for information retrieval. These perceptions that the EHR is a “shift behind” may lead to a further reliance on verbal information exchange, which is a valuable clinical communication activity, yet, is subject to information loss.Conclusions: Electronic documentation tools that, in real time, capture information that is currently verbally communicated may increase the effectiveness of communication.
Keywords: ICU; communication; interdisciplinary; electronic health record